供基于显微术的尿沉渣分析仪使用的质量控制物质及其使用方法 (2022)
本文提供了供基于显微术的尿沉渣分析仪使用的质量控制物质。所述质量控制物质包含尿基质和癌细胞、藻类细胞、酵母细胞、卵清或其任何组合。还提供了检测来自主体的尿样品中分析物的存在的方法，供鉴定来自主体的尿样品中一种或多种分析物的存在之用的质量控制物质，以及癌细胞、藻类细胞、酵母细胞、卵清或其任何组合在制备供基于显微术的尿分析仪使用的质量控制物质中的用途。 Provided herein are quality control substances for use with a microscopy-based urine sediment analyzer. The quality control substances comprise a urine matrix and a cancer cell, an algae cell, a yeast cell, egg white, or any combination thereof. Methods of detecting the presence of an analyte in a urine sample from a subject, quality control substances for use in identifying the presence of one or more analytes in a urine sample from a subject, and the use of a cancer cell, an algae cell, a yeast cell, egg white, or any combination thereof in the manufacture of a quality control substance for use with a microscopy-based urine analyzer are also provided.